Streeter's 'Other' Synoptic Solution: The Matthew Conflator Hypothesis*. (29th February 2016) - Garrow, Alan
Abstract : B. H. Streeter's Four Gospels has had a critical influence on the study of the Synoptic Problem. Unfortunately, this seminal work rests on two fundamental errors. When these are corrected, however, Streeter points to a fully satisfying solution to the Synoptic Problem: Mark wrote first, Luke used Mark and other sources and, at a later date, Matthew conflated Mark, Luke and other sources – including some also used by Luke.